Floristic diversity of the steppe area of Tissemsilt, Northwest of Algeria - LAÏD GUEMOU; SAHNOUNE FELLAH; MOHAMED MAIRIF; KADDA MOHAMED LAMINE CHOUHIM; BADREDDINE MOUSSAOUI; IKRAM NOURELHOUDA BOUZEMARENE; CHAHINEZ BOUBEKEUR (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Guemou L, Fellah S, Mairif M, Chouhim KML, Moussaoui B, Bouzemarene IN, Boubekeur C. 2023. Floristic diversity of the steppe area of Tissemsilt, Northwest of Algeria. Biodiversitas 24: 2483-2491. This study uses a stigmatist phytoecological technique to survey and evaluate the plant diversity of the Tissemsilt steppe region. The floristic analysis allowed us to draw up a list of 105 taxa, including 86 genera distributed across 34 families with a dominance of Asteraceae (24.76%), Poaceae (9.5%), and Fabaceae (8.6%). The comparison of the different biological types showed the importance of Therophytes (51.42%) that adapt well to environmental conditions. On the biogeographical level, our study affirmed the affinity of the Algerian steppe vegetation with the Mediterranean flora. The methodology adopted for the biodiversity measurement through the flora analysis using several ecological indexes has disclosed an important diversity through the Shannon index (4.96). At the same time, the Evenness of Pielou indicated regularity in the distribution of species (0.73). However, the perturbation index (63.8%) revealed an environment opening. It confirmed the presence of the phenomenon of Therophytization in this region by the dominance of Therophytes annual species more or less needing trophic, water resources and opening areas.